The corporate governance and efficiency of commercial banks in Pakistan: application of the non-parametric approach - Iftikhar, Umer; Asghar, Muhammad Jam e Kausar Ali; Khan, Hamad; Mirza, Hammad Hassan (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
This study examined the relationship of Corporate Governance (CG) on the efficiency of commercial banks listed on the Pakistan Stock Exchange (PSX) over the period from 2005 to 2014. The CG of commercial banks is measured with the composite CG index which is further subdivided into: board of directors, audit committee, disclosure and transparency, remuneration committee and shareholder’s rights. The Data Envelopment Analysis (DEA) approach is used to measure the technical efficiency (TE) and cost efficiency (CE) whereas the Tobit regression model is used to investigate the relationship between CG and both efficiency scores. The results for the composite CG index suggest that there is a positive and significant relationship of CG with both TE and CE of commercial banks. Moreover, the sub-indices also validate our results as they were mostly found positively and significantly associated with both efficiencies
Argumenta Oeconomica, 2019, Nr 2 (43), s. 169-189
Keywords: CG index; technical efficiency; cost efficiency; DEA; commercial banks